Sex matching does not impact the outcome after simultaneous pancreas‐kidney transplantation. Issue 11 (4th October 2019) - Messner, Franka; Etra, Joanna W.; Haugen, Christine E.; Bösmüller, Claudia; Maglione, Manuel; Hackl, Hubert; Riedmann, Marina; Oberhuber, Rupert; Cardini, Benno; Resch, Thomas; Scheidl, Stefan; Margreiter, Raimund; et al.
Abstract: Background: Several studies in solid organ transplantation have shown a correlation between donor and recipient sex mismatch and risk of graft loss. In this study, we aimed to analyze the impact of donor and recipient sex matching on patient and pancreas graft survival in a large single‐center cohort. Methods: We retrospectively analyzed all first simultaneous pancreas‐kidney transplants performed between 1979 and 2017 at the Medical University of Innsbruck. Results: Of 452 patients, 54.6% (247) received a sex‐matched transplant. Patient survival ( P  = .86), death‐censored pancreas graft survival (dcPGS, P  = .26), and death‐censored kidney graft survival (dcKGS, P  = .24) were similar between the sex‐matched and sex‐mismatched groups. Patient survival and dcPGS at 1, 5, and 15 years were 95.9%, 90.0%, and 62.1% and 86.1%, 77.1%, and 56.7% in the sex‐matched group and 93.6%, 86.2%, and 62.4% and 83.1%, 73.3%, and 54.3% in the sex‐mismatched group. Sex matching led to a lower odds of severe postoperative complications (41.2% vs 49.0%; OR 0.57, 95%CI 0.33‐0.97; P  = .038); however, no increased odds of other adverse postoperative outcomes was detected. Conclusion: Our study demonstrates that sex matching reduced the odds of postoperative complications but did not impact other early and late outcome parameters in our cohort.